Impact of Sex and Exercise on Femoral Artery Function: More Favorable Adaptation in Male Rats - Márton Vezér; Attila Jósvai; Bálint Bányai; Nándor Ács; Márton Keszthelyi; Eszter Soltész-Katona; Mária Szekeres; Attila Oláh; Tamás Radovits; Béla Merkely; Eszter M. Horváth; György L. Nádasy; et al. (Life, 2023)
Blood flow increases in arteries of the skeletal muscles involved in active work. Our aim was to investigate the gender differences as a result of adaptation to sport in the femoral arteries. Vascular reactivity and histology of animals were compared following a 12-week swimming training. Animals were divided into sedentary male (MS), trained male (MTr), sedentary female (FS), and trained female (FTr) groups. Isolated femoral artery rings were examined by wire myography. Contraction induced by phenylephrine (Phe) did not differ between the four groups. The contractile ability in the presence of indomethacin (INDO) was decreased in both sedentary groups. However, we found a specific cyclooxygenase-2 (COX-2) role only in FS rats. After exercise training, we observed increased vasoconstriction in both sexes, when nitro-L-arginine methyl ester (L-NAME) was present. The COX-dependent vasoconstriction effect disappeared in MTr animals, and the COX-2-dependent vasoconstriction effect disappeared in FTr ones. Relaxation was reduced significantly, when L-NAME was present in MTr animals compared to in FTr rats. The training was associated with greater endothelial nitric oxide synthase (eNOS) protein expression in males, but not in females. The present study proves that there are gender differences regarding adaptation mechanisms of musculocutaneous arteries to sports training. In males, relaxation reserve capacity was markedly elevated compared to in females.